APLIKASI PENCARIAN ALAMAT TUJUAN BERBASIS ANDROID (STUDI KASUS DAERAH BANDA ACEH) - Abdul Rahman; Zalfie Ardian (Ubudiyah Indonesia University, 2019)
The large number of addresses that do not response make people confused to find their destination addresses with ease. So often someone getting lost or wrong destination in the search for addresses. Banda Aceh became one of the cities with high visitor levels in Aceh. Of course not everyone can know all the addresses of government offices, hospitals and schools in Banda Aceh. By looking at the problems that have been found above, can be given a solution with builds an Android-based application that serves as a medium of information to search for the destination address. It needs a system that can accommodate any type of address it into one, so that when someone wants to find the destination address, it can easily find detailed information, with quick, precise, and accurate. Simply by typing in keywords in a Search engine's search menu that becomes available, then the system will process the database to match the right keywords so found and according to the expectations of the users. This application is formed above the JAVA programming language as the algorithms and data structures and XML programming language as the language of the form interface or layout application. The exchange of data on the application form the above JSON using PHP programming language later in the java programming language captures the results of a data comes from the database in the form of JSON. Expected with the search applications this address can make it easier to seek and find the destination address with ease. Keywords : Address, Android, JAVA, JSON, PHP